(untitled) (Journal of International Studies, 2020)
In the last ten years, the world has witnessed much debate on new forms of the global phenomena of fundamentalism and extremism. It is clear that many view Muslims as â€œthe otherâ€ or outsider and vice-versa; an attitude of â€œus and themâ€, â€œour community and their communityâ€. The concept of a â€˜clash of civilisationsâ€™ has become part of our everyday vocabulary. The objective of this article is namely to develop the theory of Aman (peaceful co-existence and mutual respect) as a Muslim contribution to normative considerations in international relations theory. It is found that the main four components of this theory are: the methodology of Tadafuâ€™ (counteraction), the concept of Adil (justice), the principle of not excluding others, and the constructive argumentation methodology. The theory has been tested and implemented by examining, in particular, Umar Assurance of Aman and the negotiations between Salah al-Din and King Richard I â€˜the Lionheartâ€™ of England over Islamicjerusalem in 1191. It is hoped that this theory could help place Muslim contributions in the epitome of global discourse of international relations theory, set the scene to advance the current research on the Muslim contributions to international relations theory including peace study and conflict resolution, and open up and promote intellectual and academic debate and understanding of this Muslim contributions to shed light on new lines of explanation. Although Islamicjerusalem is the most delicate issue of dispute between the current two conflicting parties, it is hoped that this theory will provide a better understanding for the world leaders who are trying to return peace to the region.